Svetlana, doch' Iosifa . Svetlana, doch' Iosifa . Svetlana, Joseph's Daughter . Светлана, дочь Иосифа - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. A documentary about Svetlana Allilueva, Joseph Stalin's daughter. (Part 1) Featured in the program: Allilueva, Svetlana (Joseph Stalin's daughter) Contributors: Nikishin, Andrei (Director) Документальный фильм о Светлане Аллилуевой, дочери Иосифа Сталина. (Часть 1). В программе участвуют: Аллилуева, Светлана (Дочь Иосифа Сталина) Создатели: Никишин, Андрей (Режиссер)